2019
DOI: 10.1002/stem.3044
|View full text |Cite
|
Sign up to set email alerts
|

IDO1 Maintains Pluripotency of Primed Human Embryonic Stem Cells by Promoting Glycolysis

Abstract: Human embryonic stem cells (hESCs) depend on glycolysis for energy supply and pluripotency and switch to oxidative phosphorylation upon differentiation. The underlying mechanisms remain unclear. Here, we demonstrate that indoleamine 2,3-dioxygenase 1 (IDO1) is expressed in primed hESCs and its expression rapidly downregulated upon hESC differentiation. IDO1 is required to maintain pluripotency by suppressing mitochondria activity and promoting glycolysis through the increase of NAD + /NADH ratio. The upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…NAD + regulation has been shown to be necessary for both the acquisition and maintenance of human and mouse ESC pluripotency . In hESCs, a 50% reduction in NAD + by inhibiting nicotinamide phosphoribosyltransferase (NAMPT) activity causes spontaneous differentiation and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD + regulation has been shown to be necessary for both the acquisition and maintenance of human and mouse ESC pluripotency . In hESCs, a 50% reduction in NAD + by inhibiting nicotinamide phosphoribosyltransferase (NAMPT) activity causes spontaneous differentiation and apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…pluripotency. [17][18][19] In hESCs, a 50% reduction in NAD + by inhibiting nicotinamide phosphoribosyltransferase (NAMPT) activity causes spontaneous differentiation and apoptosis. 20 Furthermore, ESCs and induced pluripotent stem cells (iPSCs) are reliant on, and have higher levels of, NAD + salvage enzymes compared with their differentiated counterparts.…”
mentioning
confidence: 99%
“…Liu et al recently reported that IDO1 mediated the maintenance of pluripotency in human embryonic stem cells [ 26 ] and led us to investigate the potential regulatory activity of IDO1 in Notch1 expression. With the lentiviral delivery of IDO1 specific shRNAs ( Figure 5 A) or the treatment of INCB-024360 ( Figure 5 B), the inhibition of IDO1 in HeLa and SiHa tumorspheres caused the downregulation of NICD.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, suppression of mitochondrial respiration is beneficial to maintain the pluripotency. Indeed, either promotion of glycolysis or suppression of oxidative phosphorylation can accelerate the reprogramming process during which somatic cells are converted into induced pluripotent stem cells (iPSCs) [ 44 ]. Considering the hypoxic condition in the uterus, it is not surprising that ESCs—the in vitro counterpart of inner cell mass in the early embryo—prefer glycolysis.…”
Section: Redox Biology In the Cellsmentioning
confidence: 99%